On a hybrid MPPT control scheme to improve energy harvesting performance of traditional two-stage inverters used in photovoltaic systems. (March 2017) - Jiang, Joe-Air; Su, Yu-Li; Kuo, Kun-Chang; Wang, Chien-Hao; Liao, Min-Sheng; Wang, Jen-Cheng; Huang, Chen-Kang; Chou, Cheng-Ying; Lee, Chien-Hsing; Shieh, Jyh-Cherng
Abstract: How to promote the energy harvesting performance of traditional two-stage inverters used in photovoltaic (PV) systems is a critical issue in the PV applications. This paper reviews the prevalent maximum power point tracking (MPPT) techniques and the difficulties and performances of using different stage inverter architectures. Based on the findings of the reviews, this study proposes a new hybrid MPPT algorithm to speedily track the MPP of the PV arrays. The algorithm can be used in a single-phase two-stage PV inverter, where the direct current (dc) sensors for tracking the MPP are not required. A current mode control with a phase-locked function is also proposed to combine with the hybrid MPPT method and implemented in the PV inverter. A grid-tied PV power conditioning (PVPC) system with a capacity rating of 4 kW was constructed as a test sample system. An extensive series of experiments were conducted to examine the basic performance for tracking the dynamic MPP of PV array provided by the proposed method. The test results show that the proposed hybrid MPPT method could produce more energy of 2.72% than the traditional P&O method. Moreover, the comparative experiments for several kinds of microprocessor- and digital signal processor (DSP)-based commercial inverters using different MPPT methods were also conducted. Experimental results demonstrate that the commercial inverter equipped with the proposed hybrid MPPT algorithm has a better energy harvesting performance comparing to other commercial inverters with various MPPT methods. The developed hybrid MPPT algorithm and control scheme are promisingly in energy harvest and are ready to use in the commercial PV systems.